Die korinthische Gemeinde als Nebenadressat des Römerbriefs: Eigentextreferenzen des Paulus und kommunikativer Kontext des längsten Paulusbriefes - Hartwig, Charlotte; Theißen, Gerd (Novum Testamentum, 2004)
The letter to the Romans is not only addressed to the Romans as the main addresses but indirectly to the Corinthians. When Paul was writing this letter he lived in the Corinthian congregation, continuing his dialogue with the Corinthians. This is why Paul reworked some topics from 1 and 2 Corinthians in order to correct them and to put them more exactly. The letter is thus embedded in his written and oral communication with the Corinthians. The Corinthians could understand some hints and allusions much better than the Romans.